1995
DOI: 10.1038/ki.1995.488
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 inhibits cytokine-stimulated transcription of inducible nitric oxide synthase in glomerular mesangial cells

Abstract: Endothelin-1 (ET-1) is a potent vasoconstrictor while nitric oxide (NO) has strong vasodilatory effects. Recent studies have indicated that vasoconstrictors and NO may mutually modulate their production and/or activity, thus regulating each other in the context of microcirculatory maintenance. We examined the question whether ET-1 may affect NO formation by controlling the expression of the inducible isoform of the NO synthase (iNOS) in cultured rat glomerular mesangial cells (MCs), as induced by the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…This renders the elucidation of a universal signaling pathway for iNOS regulation more difficult. Cloning of murine [18], human [19,20] and rat iNOS promoters has enabled us to examine transcriptional effects with authentic promoter fragments.We have recently reported that ET-1 inhibits iNOS expression induced by TNF-c~ and IL-I[3 via the ETA receptor in rat MCs [17]. Our data indicated that the inhibition occurs at the transcriptional level.…”
supporting
confidence: 55%
“…This renders the elucidation of a universal signaling pathway for iNOS regulation more difficult. Cloning of murine [18], human [19,20] and rat iNOS promoters has enabled us to examine transcriptional effects with authentic promoter fragments.We have recently reported that ET-1 inhibits iNOS expression induced by TNF-c~ and IL-I[3 via the ETA receptor in rat MCs [17]. Our data indicated that the inhibition occurs at the transcriptional level.…”
supporting
confidence: 55%
“…The ability of MC to enhance production of nitrite and expression of the iNOS in response to these proinflammatory cytokines have been reported by many groups, including ourselves [15][16][17]. Results of some of these studies [16,17], by indicating that co-stimulation of mesangium with IL-1 and TNF-acts synergistically to generate large amounts of nitrite, prompted us to utilize concurrently both cytokines in our experiments. MC stimulated to proliferate with bFGF did not in our hands respond as vigorously by production of nitrite to stimulation with IL-1 and TNF-as did quiescent cells, contrary to vascular smooth muscle cells, which more remarkably enhance generation of NO 2 -upon triggering with IL-1 and bFGF, as described by Scott-Burden et al [19].…”
Section: Discussionmentioning
confidence: 91%
“…We (Beck et al [16]) and others [17] have previously reported that co-stimulation of cultured mesangial cells with IL-1 and TNFresults in generation of greater quantities of nitrite than when cells are stimulated with either cytokine alone. In the present experiments triggering quiescent mesangial cells with IL-1 and TNFcaused a remarkable increase in nitrite production, inhibitable by L-NMMA as depicted in Fig.…”
Section: Effect Of Endogenously Produced No On 3 H-thymidine Uptake Bmentioning
confidence: 89%
“…iNOS-like immunoreactivity was also demonstrated in glandular epithelial cells, but eNOS and iNOS could not be detected in human endometrial stromal cells by immunocytochemical methods (27). On the other hand, although several studies have focused on the effect of ET on NO production in glomerular mesangial cells (28,29) and vascular smooth muscle EUROPEAN JOURNAL OF ENDOCRINOLOGY (1998) 138 Figure 1 Effect of IL-1b and LNMMA on ET-1 release from cultured human endometrial stromal cells in the first (A), second (B) and third (C) 24 h culture. Cells were incubated with or without IL-1b in the absence or presence of LNMMA at 37 ЊC in RPMI 1640 medium without fetal bovine serum.…”
Section: Discussionmentioning
confidence: 99%